EVALUASI ERGONOMI DAN ESTETIKA GAGANG WAJAN: STUDI EKSPERIMEN PADA BERBAGAI WAJAN - Abadi, Starletto; Sukania, I Wayan; Utama, Didi Widya (Universitas Tarumanagara, 2025)
The pan handle is a crucial component that influences the comfort, safety, and user perception of cookware. However, existing market designs often compromise on one of two fundamental aspects: ergonomics or aesthetics. This study aims to (1) evaluate the ergonomic and aesthetic aspects of ten different commercial pan handle designs, (2) analyze the correlation between these two aspects, and (3) apply the findings to design and validate a new, superior concept. An experimental method with a within-subject design involved 30 participants who performed a series of simulated use tasks and provided subjective ratings using a Likert scale. Data were analyzed using the Friedman test with a post-hoc Wilcoxon Signed-Rank test, and Spearman's rank correlation. The results showed highly statistically significant differences in the ergonomic (χ²(9) = 257.300, p < .001) and aesthetic (χ²(9) = 238.920, p < .001) ratings. Furthermore, a very strong and highly significant positive correlation was found between perceived ergonomics and aesthetics (ρ = .900, p < .001). These findings were then successfully applied to develop a physical prototype, which was validated with an ergonomic comfort score of 4.07 and an aesthetic score of 4.33. This research provides important implications for the holistic design of pan handles, emphasizing that the integration of functional and visual considerations is crucial for enhancing the overall user experience.